The effect of fieldwork experience on the nature of clinical reasoning skills in third year occupational therapy students at the University of Durban-Westville - Pretorius, B.(Blanche) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1998.